Mapping of quantitative trait loci for yield, quality and disease resistance - Williams, Kevin; Willsmore, Kerrie; Hoppo, Sue; Eckermann, Paul; Zwer, Pamela (MTT, 2004)
A genetic map was produced to identify loci contributing to disease resistance, quality and yield of oat. An F8 single-seed descent population of 170 lines was produced from the cross Potoroo x Mortlock. This population segregated for several disease resistances derived from the dwarf feed variety Potoroo and a number of quality traits contributed by the tall milling quality variety Mortlock. The F8 lines were evaluated for 35 agronomic, quality and disease resistance traits at three sites for up to three years. A genetic map of 24 linkage groups covering 2145 cM was produced using this population. The map currently consists of 45 RFLP, 14 SSR and 381 AFLP markers. Quantitative Trait Loci (QTLs) for cereal cyst nematode resistance and tolerance were identified. A single nucleotide polymorphism assay was developed for one of these loci. Two major QTLs for yield were observed, both contributed by Potoroo. Two major QTLs were found to control the quality characteristics of Mortlock, with one linked in repulsion to a dwarfing gene in Potoroo. A number of QTLs contributed to grain weight, oil content and protein levels. A summary of the major QTLs, their interactions and the opportunities to combine them to obtain the desired breeding outcomes will be presented.
Keywords: Ka; molecular markers; genotyping; stem nematode; digital imaging